Interhemispheric control of sensory cue integration and self-motion perception - Arshad, Qadeer; Ortega, Marta Casanovas; Goga, Usman; Lobo, Rhannon; Siddiqui, Shuaib; Mediratta, Saniya; Bednarczuk, Nadja F.; Kaski, Diego; Bronstein, Adolfo M. (Neuroscience, 2019)
Spatial orientation necessitates the integration of visual and vestibular sensory cues, in-turn facilitating self-motion perception. However, the neural mechanisms underpinning sensory integration remain unknown. Recently we have illustrated that spatial orientation and vestibular thresholds are influenced by interhemispheric asymmetries associated with the posterior parietal cortices (PPC) that predominantly house the vestibulo-cortical network. Given that sensory integration is a prerequisite to both spatial orientation and motion perception, we hypothesized that sensory integration is similarly subject to interhemispheric influences. Accordingly, we explored the relationship between vestibulo-cortical dominance – assessed using a biomarker, the degree of vestibular-nystagmus suppression following transcranial direct current stimulation over the PPC – with visual dependence measures obtained during performance of a sensory integration task (the rod-and-disk task). We observed that the degree of visual dependence was correlated with vestibulo-cortical dominance. Specifically, individuals with greater right hemispheric vestibulo-cortical dominance had reduced visual dependence. We proceeded to assess the significance of such dominance on behavior by correlating measures of visual dependence with self-motion perception in healthy subjects. We observed that right-handed individuals experienced illusionary self-motion (vection) quicker than left-handers and that the degree of vestibular cortical dominance was correlated with the time taken to experience vection, only during conditions that induced interhemispheric conflict. To conclude, we demonstrate that interhemispheric asymmetries associated with vestibulo-cortical processing in the PPC functionally and mechanistically link sensory integration and self-motion perception, facilitating spatial orientation. Our findings highlight the importance of dynamic interhemispheric competition upon control of vestibular behavior in humans.